2002
DOI: 10.2165/00003495-200262150-00001
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring in the Treatment of Tuberculosis

Abstract: Therapeutic drug monitoring (TDM) is a standard clinical technique used for many disease states, including many infectious diseases. As for these other conditions, the use of TDM in the setting of tuberculosis (TB) allows the clinician to make informed decisions regarding the timely adjustment of drug therapy. Such adjustments may not be required for otherwise healthy individuals who are responding to the standard, four-drug TB regimens. However, some patients are slow to respond to treatment, have drug-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
398
5
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 388 publications
(428 citation statements)
references
References 68 publications
19
398
5
6
Order By: Relevance
“…The analytical range was based on clinical pharmacokinetic data and set at 0.2-8 mg/L for isoniazid and ethambutol and 2-80 mg/L for pyrazinamide [3,16]. As stable isotope-labelled internal standards are known to compensate for matrix effects [9,10], isoniazid-D4 and ethambutol-D4 were used as such.…”
Section: Methods Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical range was based on clinical pharmacokinetic data and set at 0.2-8 mg/L for isoniazid and ethambutol and 2-80 mg/L for pyrazinamide [3,16]. As stable isotope-labelled internal standards are known to compensate for matrix effects [9,10], isoniazid-D4 and ethambutol-D4 were used as such.…”
Section: Methods Developmentmentioning
confidence: 99%
“…Recently, Pasipanodya et al showed that risk on treatment failure was almost nine fold higher in patients with low drug exposure compared to patients with higher drug exposure [2]. Therefore, monitoring of drug exposure in patients at risk for low drug exposure is worthwhile to explore in a prospective manner [3]. To be able to evaluate drug exposure a fast, accurate and simple method for determination of isoniazid, rifampin, pyrazinamide and ethambutol in serum is valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic and pharmacodynamic markers of antituberculosis drugs for the use of therapeutic drug monitoring [7,10,[18][19][20].…”
Section: Efficacymentioning
confidence: 99%
“…WHO group [21] Drug Adult daily dose* [7,18,20] C max [7,18,20] T max (h) [7,18,20] PK/PD b [7,18,20] PK/PD target value [19,22] The adult dosage is based on the dosage that is given a day, while dosing multiple times a day is not performed very often anymore because of compliance.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation